Classification of methods and instruments of government financial regulation of households socio-economic inequality - M. L. Dorofeev (Вестник университета)
One of the most dangerous risks of growing socio-economic inequality is the ability of the latter to that it can transform into political inequality, initiate the creation of extractive economic institutions and lead to the degradation of the country’s development. The article provides a critical analysis of the modern classification of instruments of economic inequality regulation presented at the Peterson Institute conference in 2019. Based on this concept, an expanded and more universal classification of methods and tools is proposed, and the most relevant ones are discussed taking into account modern realities. In conclusion, we gave recommendations for the Governments of developed and developing countries concerning the priorities in choice of methods and instruments of socio-economic inequality regulation in order to avoid an increase in excessive economic inequality and subsequent socio-economic problems.